2017
DOI: 10.1007/978-3-319-70111-0
|View full text |Cite
|
Sign up to set email alerts
|

Serious Games

Abstract: Domestic violence is a persistent and universal problem occurring in every culture and social group, with lack of empathy identified as a contributing factor. On average, one in three women and girls in the Caribbean experience domestic violence in their lifetime. In this paper we demonstrate the techniques used during the creation of a low-cost, violence prevention game titled None in Three, targeted at enhancing empathy and awareness among young people in Barbados and Grenada. A research trip was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…To accomplish this, they utilize a combined 'Learning Mechanics -Game Mechanics' (LM-GM) model and further add VR characteristics. The study found that VRSGs improve the presence, immersion, and cognitive performance of users as the VR component reinforces players' embodied cognition through a purposeful and interactive design [10]., VR offers additional gaming experiences that don't translate to traditional computerized games.…”
Section: Serious Games and Attention (Cognitive Skills)mentioning
confidence: 96%
See 2 more Smart Citations
“…To accomplish this, they utilize a combined 'Learning Mechanics -Game Mechanics' (LM-GM) model and further add VR characteristics. The study found that VRSGs improve the presence, immersion, and cognitive performance of users as the VR component reinforces players' embodied cognition through a purposeful and interactive design [10]., VR offers additional gaming experiences that don't translate to traditional computerized games.…”
Section: Serious Games and Attention (Cognitive Skills)mentioning
confidence: 96%
“…The study concluded that the Open Learner Model is effective in personalizing the user's experience, guaranteeing transparency, and helping users selfregulate their skills. Furthermore, in [10], the authors took it one step further by approaching SGs for improving cognitive functions through the lens of Virtual Reality (VR). Thus, their study explored Virtual Reality Serious Games (VRSGs) to optimize the cognitive performance of users.…”
Section: Serious Games and Attention (Cognitive Skills)mentioning
confidence: 99%
See 1 more Smart Citation
“…A game has an element of entertainment and is enjoyable. However, by prioritizing specific purposes other than entertainment, a game can be used to facilitate other purposes such as training, advertising, simulation, and education [1]- [3]. This type of game is called a serious game.…”
Section: Introductionmentioning
confidence: 99%
“…In chemistry education, much work has been done regarding alternative memorization methods, including concepts and strategies such as “learning by playing”, “edutainment”, or “serious games”, i.e., games designed for a primary purpose other than pure entertainment. The games can be developed either in a physical format, a digital format, , or both .…”
Section: Introductionmentioning
confidence: 99%